Morphological Changes of Anterior Cerebral Artery (ACA) in Hydrocephalic Pediatric Patients - OZTURK, Sait; AYAN, Erdogan; KAPLAN, Metin (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Ozturk S, Ayan E, Kaplan M. Morphological Changes of Anterior Cerebral (ACA) Artery in Hydrocephalic Pediatric Patients. Iran J Child Neurol. Winter 2017; 11(1):37-42. Abstract Objective The morphology of anterior cerebral artery (ACA) in patients with hydrocephalus (HCP) was analyzed, and its importance was discussed in maintaining cerebral perfusion. Materials & Methods A total of 84 cases in 2 groups between 0 and 3 months, followed-up at Firat Universitesi Hastanesi, Beyin Cerrahisi Klinigi, Elazig, Turkiye due to in 2010-2013, were enrolled. Two groups were created for the study. Group 1; patients with HCP and Group 2; as control group without HCP. In both groups, the length of the A2 segment of ACA was measured from its origin to the junction of the genu and body portions of the corpus callosum on T2 mid-sagittal magnetic resonance (MR) scans. For all cases, axial MR imaging scans were used to calculate Evans’ index (EI), and the cases were divided into three groups: Group A, EI ≥50%; Group B, EI of 40-50% and Group C, EI <40%. The two groups (Groups 1 and 2) were compared with respect to ACA length, and the correlation with the EI was quantified. P values below 0.05 were considered statistically significant. Results Mean length of ACA was 57.3 mm in Group 1 and 37.5 mm in Group 2. EI increased as the length of ACA increased. A statistical comparison of the two groups revealed that the ACA length was significantly greater in Group 1. The relationship between EI and ACA length was statistically significant. Conclusion Reducing ventricular size appears to be an important factor in addition to reducing intracranial pressure in an attempt to maintain normal cerebral perfusion(CP). References 1. Westra SJ, Lazareff J, Curran JG, Sayre JW, Kawamoto H Jr. Transcranial Doppler ultrasonography to evaluate need for cerebrospinal fluid drainage in hydrocephalic children. J Ultrasound Med 1998; 17): 561-569. 2. Kolarovszki B, Zubor P, Kolarovszka H, Benco M, Richterova R, Matasova K. The assessment of intracranial dynamics by transcranial Doppler sonography in perioperative period in paediatric hydrocephalus. Arch Gynecol Obstet 2013; 287: 229-238. 3. Tritton DJ. Fluid Mechanics. Physical fluid Dynamics. Tritton, DJ: 2nd ed. Oxford, Clarendon Press 1988; pp:536-540. 4. de Oliveira RS, Machado HR. Transcranial color-coded Doppler ultrasonography for evaluation of children with hydrocephalus. Neurosurg Focus 2003; 15: ECP3. 5. Kempley ST, Gamsu HR. Changes in cerebral artery blood flow velocity after intermittent cerebrospinal fluid drainage. Arch Dis Child 1993; 69: 74-76. 6. Hanlo PW, Gooskens RH, Nijhuis IJ, Faber JA, Peters RJ, van Huffelen AC and et al. Value of transcranial Doppler indices in predicting raised ICP in infantile hydrocephalus. A study with review of the literature. Childs Nerv Syst 1995; 11: 595-603. 7. Nishimaki S, Yoda H, Seki K, Kawakami T, Akamatsu H, Iwasaki Y. Cerebral blood flow velocities in the anterior cerebral arteries and basilar artery in hydrocephalus before and after treatment. Surg Neurol 1990; 34: 373- 377. 8. Wang B, Cheng Z, Mu X, Fan B, Guo Z. Preoperative and postoperative transcranial Doppler sonographic evaluations of the cerebral hemodynamics of craniostenosis. J Craniofac Surg 2010; 21: 432-435. 9. Bell SR, Vo AH, Armanda RA. Applied neurovascular anatomy of the brain and skull. In: Hurst RW, Rosenwasser RH, editors. Interventional Neuroradiology. New York: Informa; 2008: pp: 22-27. 10. Kaplan M, Berilgen MS, Erol FS, Artas H, Serhatlioglu S, Ozveren MF. Relationship between Clinical Grade, Cerebral Blood Flow, and Electroencephalographic Alterations in Patients with Chronic Subdural Hemorrhage. Neurosurgery Q 2006; 16: 157-160. 11. Riggo JD, Kolarovszki B, Richterova R, Kolarovszka H, Sutovsky J, Durdikc P. Measurement of the blood flow velocity in the pericallosal artery of children with hydrocephalus by transcranial Doppler ultrasonography-preliminary results. Biomed Pap Med Fac Univ Palacky Olomouc Czech Repub 2007; 151: 285-289. 12. Zenger MN, Kabataş S, Zenger S, Cakmakçi H. The value of power Doppler ultrasonography in the differential diagnosis of intracranial extraaxial fluid collections. Diagn Interv Radiol. 2007; 13: 61-63. 13. Kaplan M, Erol FS, Bozgeyik Z, Koparan M: The effectiveness of simple drainage technique in improvement of cerebral blood flow in patients with chronic subdural hemorrhage. Turk Neurosurg 2007; 17: 202-206. 14. Rozenfeld A. Ultrasound in diagnostics of blood vessels: the role of the assessment of both extra- and intracranial flows by Doppler ultrasonography. Neurol Neurochir Pol 1994; 28: 51-66. 15. Miller SP, Cozzio CC, Goldstein RB, Ferriero DM, Partridge JC, Vigneron DB and et al. Comparing the diagnosis of white matter injury in premature newborns with serial MR imaging and transfontanel ultrasonography findings. AJNR Am J Neuroradiol 2003; 24: 1661-1669.